Decolonizing Methodologies: Ethics of Infrastructure Development in the Rural - Himalaya Ahuja (Ibn Haldun University, 2019)
The Prime Minister of India marked 28th April 2018 as a historic day in the journey of Indian development. Through a tweet, he claimed that on this day electricity has reached to each and every village in India. Taking this claim as a starting point, this paper looks into Rural Electrification and Politics of Infrastructure in Khannat, a village in south east of Madhya Pradesh. This paper is a reflection on a collaborative action research on rural electrification in the village Khannat. It proposes to show how this intervention cannot merely be read as an intervention around energy and Infrastructure. It shows that through the tropes of rural electrification, how ‘infrastructure’ can be a method to revisit village studies. Infrastructure in the history of development thought has been tied to the idea of ‘growth’ and ‘modernity’. This work is based on a methodology that is premised on knowledge production through immersion in a ‘local’ world. However, ‘infrastructure’ is a concept that is clearly ‘translocal’. Thus, it aims to unpack the ethnocentric view of infrastructure and explore if the community can produce its own idiom of infrastructure. Through rural electrification, this paper aims to critique the way Infrastructure Development is undertaken in rural India and how local meanings of infrastructure are completely ignored.